Inovasi Fiber Optik untuk Pembuatan Dinding Beton Transparan - Tubagus Fachrizal; Puji Widodo; Bambang Setiabudi (Universitas Diponegoro, 2023)
Research in the site of construction is currently focused on utilization of unique, innovative, and cost-effective construction materials for long-term purposes, particulary in the context of green buildings. One material that has gained attention is tralucent concrete or light-transmitting concrete, which employs nano-optic concepts and fiber optic to transmit external light through its internal spaces. This study present a comprehensive review of previous research on light-transmitting concrete, specifically examining its applications, optimalization fiber ratios, and arrangement. Furthermore, the investigation delves into the propertiesencompassing liht transmission, mechanical strength, and energy efficiency of transparent concrete. To maximize light transmission, various proportion of fiber optic, count 3%, 4%, and 5% were incorporated into the concrete mixture. As aresult, this study aims to identify differet types of transparent materials, elucidate their properties and offer pratical illustration and application to addres these research gaps. Indeed, this research contributes to advancement of innovative construction materials, which have potential to enhance energy efficiency .